Do We Know Organic Food Consumers? The Personal and Social Determinants of Organic Food Consumption - Sevtap Ünal; F. Görgün Devecİ; Tuğba Yildiz (Istanbul Business Research (IBR), 2019)
The main aim of this study is determining which consumption motives and personal and social factors affect organic food buying decisions. Ajzen's Planned Behavior Theory (TPB) is used to explain consumers' organic food selection behaviors. In addition, the moderating role of uncertainty about organic foods and the mediating role of the price of organic foods were tested. Data were gathered via a survey of consumers of organic foods in Turkey. The research model was tested by Structural Equation Modeling (SEM) via Smart PLS3. The findings showed that consumptions motives of healthiness, easiness, mood, and convenience-price of organic foods motivate consumers to buy organic foods. In addition, environmental concern and negative emotions influence on attitudes towards organic foods and purchase intentions. On the other hand, subjective norms and self-monitoring do not influence attitudes towards organic foods and subsequent purchase intentions. Uncertainty has a moderating effect on the relationship between attitudes and purchase intentions whereas price has no mediating effect on the relationship between attitudes and purchase intentions.
Keywords: M0; 650; Organic food; Consumption motivations; Environmental concern; Consumption emotions